The Powerful and Covert Role of Culture in Gender Discrimination and Inequality. Issue 4 (4th December 2018) - Nardone, Maria
Abstract: Culture is not invisible but often exists without question and without awareness of its impact. It can be subversively complicit, unconsciously colluding, in its resistance to change. The culture of silence, complicity, and personal betrayal has allowed harassment and abuse to proliferate. The cynical belief that nothing can change obstructs change. Culture is a powerful force, invisible when you are immersed in it, but knowable and mutable. The deep structure of culture, the DNA, can be influenced through our own personal change, change that can allow us to speak out. #MeToo and #TIMESUP are individuals making a difference. For change to occur, inattention and dissociation must be replaced by the acceptance of paradox and the ability to manage it. A necessary next step in the process is dialogue. Open, mutual conversation must replace polarized scripts. Instead of viewing relationships between men and women as zero-sum games, we must see them as collaborative and mutually enhancing. Within a genuinely collaborative culture, relational power is shared. Awareness, self-reflection, and dialogue are key to developing mutuality and trust, and it is trust and mutuality that allow a collaborative culture to flourish.